Analisis Penerapan Zero Waste dalam Inovasi Batik Ecoprint Terhadap Upaya Green Entrepreneurship - Amelia Wanda Dhabitah; Dewi Kusuma Wardani; Mintasih Indriayu (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2025)
Climate change and environmental degradation have negatively impacted mankind's sustainable development. The concept of green entrepreneurship has gradually been accepted by society, including ecoprint batik. Through the application of zero waste, ecoprint batik production offers a strategy that is in line with the principles of green entrepreneurship. This study aims to analyze the application of zero waste to the efficiency of eco-print batik production in the context of green entrepreneurship. The method used in this study is a qualitative approach with secondary data collection on batik business actors in Sragen. The data obtained were then analyzed using descriptive analysis to identify the analysis of the application of zero waste in batik innovation towards green entrepreneurship efforts. The results of the study indicate that the application of zero waste in eco-print batik production has a significant impact on production efficiency, especially in reducing waste and optimizing the use of raw materials. However, there are several obstacles such as higher production costs, limited supply of natural raw materials, and low consumer awareness of the added value of zero waste-based batik. Policy support and incentive programs from the Government are also very important to encourage the sustainability of eco-print batik businesses based on green entrepreneurship.